2002
DOI: 10.1253/circj.66.349
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Clinical Outcomes Following Coronary Perforation in Patients Undergoing Percutaneous Coronary Intervention.

Abstract: hile coronary perforation is an uncommon complication following percutaneous coronary intervention (PCI), [1][2][3][4][5][6][7][8] it is one that may lead to cardiac tamponade, 6-9 emergency coronary artery bypass surgery (CABG), or pseudoaneurysm formation, 10 with the potential for late coronary rupture. New coronary devices that resect (eg, directional or transluminal extraction atherectomy), ablate (eg, rotational atherectomy or excimer laser angioplasty), or score (eg, the cutting balloon) atherosclerotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 45 publications
5
60
1
2
Order By: Relevance
“…Previous reports have demonstrated that the increase in the risk of perforation is highly associated with the use of oversized balloons, 9) stenting against eccentric, extensive, or tortuous calcified lesions, 5,7,9) and the use of atherectomy devices. 2,3,6,8,9) In the patient series analyzed in this study, in addition to the other risk factors, the use of the sirolimus-eluting stent (SES) was also found to increase the incidence of coronary perforation. The SES has been available in Japan since 2004, and all 5 perforation events (2.69%) in 2004 and 2005 occurred after deployment of the SES or during wiring for crossing the lesion that was to be treated by the drug-eluting stent.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Previous reports have demonstrated that the increase in the risk of perforation is highly associated with the use of oversized balloons, 9) stenting against eccentric, extensive, or tortuous calcified lesions, 5,7,9) and the use of atherectomy devices. 2,3,6,8,9) In the patient series analyzed in this study, in addition to the other risk factors, the use of the sirolimus-eluting stent (SES) was also found to increase the incidence of coronary perforation. The SES has been available in Japan since 2004, and all 5 perforation events (2.69%) in 2004 and 2005 occurred after deployment of the SES or during wiring for crossing the lesion that was to be treated by the drug-eluting stent.…”
Section: Discussionmentioning
confidence: 90%
“…In such cases, lesion modification with rotational atherectomy prior to stenting and a gradual increase in the pressure for inflating the stent is recommended. Although debulking devices are known to increase the risk of perforation, 2,5,6,8) we believe that this is not the case when optimal-sized rotational atherectomy is used as a pretreatment for stenting. The selection of an undersized ablation device would be optimal in such cases since the main purpose of debulking is not to obtain sufficient lumen area but to modify the calcification, which causes difficulty in stent expansion.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…If the degree of extravasation does not enlarge, or if it diminishes after this action, no further action is required. Should the extravasation enlarge, heparin reversal with protamine sulfate (1 mg per 100 units heparin) should be given intravenously, with subsequent dose titration guided by anticoagulation status (target activated clotting time <150 sec), [48,49]. Direct antithrombin agents such as bivalirudin are more problematical here as there is no simple antidote.…”
Section: Coronary Perforation And/or Rupturementioning
confidence: 99%